The Pension System in Ukraine – Some Aspects of Reforming - Furdak Marharyta M. (Bìznes Inform, 2021)
This publication is aimed at studying the processes and defining the main problems in reforming the pension system of Ukraine. The article analyzes the state of functioning and development of three levels of pension provision at the present stage of socio-economic development of the country. It is determined that only level 1 actually works in Ukraine – the solidarity system of compulsory State-controlled pension insurance, while the mandatory accumulation system has not acquired its development, and the voluntary accumulation system has an extremely low share in the general pension system. Some financial results of the Pension Fund of Ukraine for 2020 and the approved budget for 2021 are analyzed. Substantiated conclusions have been drawn about the problems of the solidarity system, such as: the existing budget deficit of the Fund, which leads to the formation of its debts; low, socially unadapted level of pensions; disparities in the size of pensions assigned in different years. The rating of currently operating non-State pension funds of Ukraine (the third level of pension provision) are analyzed according to the criteria of asset value, number of participants, amounts of pension payments and profitability, as well as the dynamics of some basic indicators of their activity. It is determined that the functioning of the non-State pension system in the country is hampered, in particular, for psychological reasons due to the population’s distrust of non-State institutions. Since the second level of pension provision – the mandatory accumulation system – has not yet started working in the country and taking into account the problems of the first and third levels, a reasonable conclusion has been made on the inhibition of the pension reform in Ukraine and the need to intensify the work on the implementation of all three levels of pension provision in order to achieve a sufficient level of social protection of citizens.